Understanding factors influencing people with disabilities' participation in sports and cultural activities - Ming Chen; Qianxue Li; Luqi Wang (BMC, 2024)
Abstract Background Improving people with disabilities' participation in sports and cultural activities benefits their physical and mental health. However, only a few studies have examined the factors that influence participation systematically. Methods Using the survey data gathered from 4,319 disabled people living in a district in Wuhan, China, this study explored the impacts of sports and cultural activity participation in terms of individual physiological characteristics, socioeconomic factors, and built environmental features. The sports and cultural facility supply and the walkability index of their community environment were calculated to assess built environment features. Binary logistic regression models were also used to investigate the influence of the aforementioned variables. Results There is a significant positive correlation between sports and cultural activity participation and education (OR = 3.44, p < 0.01), employment status (OR = 2.04, p < 0.01), as well as the number of cultural facilities (OR = 1.33, p < 0.01) in the neighborhood area. No significant association was found between the inclination to participate frequently and individual psychological factors. Conclusion Regarding people with disabilities' participation in sports and cultural activities, socioeconomic and built environment factors are more influential than individual psychological ones. The findings can give ideas for identifying targeted and comprehensive interventions to promote a healthy lifestyle for people with disabilities.